The equilibrium and fixed-bed study of malachite green adsorption on chitosan hydrogels - Song, X H (Water science and technology : a journal of the International Association on Water Pollution Research, 2019)
Chitosan hydrogel beads were prepared by a precipitation process, and were used to investigate the adsorption of malachite green (MG) oxalate under various conditions. It was found that adsorption equilibrium was most sensitive to the pH value at pH <8 while fixed bed breakthrough kinetics presented asymmetric S-shaped profiles which could not be adequately described by conventional models such as Adams-Bohart and Yoon-Nelson. The possible reasons were discussed and an improved Adams-Bohart model was proposed to better describe the changes in mass transfer mechanisms during adsorption